Paradoks Politik Pembangunan - WARJIO WARJIO (Universitas Sumatera Utara, 2014)
The concept of development and its results, is still being debated. Several theorists have demon-strated that development is a tools to reduce ppoverty and and the others consider the opposite. This study analyzes the political development and the many issues related to development. This study is using political development approach and also library research method to collect data. This study have used qualitative methods to analyze data. The results of these studies have found that the development is a global paradox. Development has varied problems and development led to imbalances world. Development also raises a moral issue, environmental damage, culture of consumerism, natural disasters and humanitarian disasters. This condition has led to the rejection will be development in some locations. There is a gap between desire and reality.Keywords: Political development, economic development, globalization.